Principles of residential space configuration / Đorđe Alfirević and Sanja Simonović Alfirević - Pucar, Mila (Arhitektura i urbanizam, 2024)
The monograph "Principles of Residential Space Configuration" represents a significant contribution to theoretical and research work in the field of architecture. The authors have successfully integrated their own and others' theoretical and design experiences, emphasising the importance of a scientific approach in architecture. The book is structured into six chapters, from an introductory definition of configuration to the analysis of specific principles, providing a deeper insight into the complexity and multi-layered nature of residential architecture. The importance of research continuity is particularly highlighted through a thorough analysis of the functional, structural, organisational, and perceptual principles of space configuration. The authors point out the need for further research to concretise parameters such as the index of polyvalence and the typology of polyvalent apartments, as well as the potential for introducing these principles into regulations. The book is an important resource in the fields of architecture and urban planning, offering an in-depth analysis of literature and practical examples. It represents an original contribution to the history and theory of design and urban planning practices, encouraging new research and the development of new principles in residential architecture.
Keywords: residential space configuration; functional principles; structural principles; organizational principles; perceptual principles